Icotinib versus chemotherapy as adjuvant treatment for stage II–IIIA EGFR-mutant non-small-cell lung cancer (EVIDENCE): a randomised, open-label, phase 3 trial. Issue 9 (September 2021) - He, Jianxing; Su, Chunxia; Liang, Wenhua; Xu, Shidong; Wu, Lin; Fu, Xiangning; Zhang, Xiaodong; Ge, Di; Chen, Qun; Mao, Weimin; Xu, Lin; Chen, Chun; et al.
Summary: Background: Icotinib has provided survival benefits for patients with advanced, epidermal growth factor receptor ( EGFR )-mutant non-small-cell lung cancer (NSCLC). We aimed to compare icotinib with chemotherapy in patients with EGFR -mutant stage II–IIIA NSCLC after complete tumour resection. Here, we report the results from the preplanned interim analysis of the study. Methods: In this multicentre, randomised, open-label, phase 3 trial done at 29 hospitals in China, eligible patients were aged 18–70 years, had histopathogically confirmed stage II–IIIA NSCLC, had complete resection up to 8 weeks before random assignment, were treatment-naive, and had confirmed activation mutation in exon 19 or exon 21 of the EGFR gene. Participants were randomly assigned (1:1) with an interactive web-based response system to receive either oral icotinib 125 mg thrice daily for 2 years or four 21-day cycles of intravenous chemotherapy (vinorelbine 25 mg/m 2 on days 1 and 8 of each cycle plus cisplatin 75 mg/m 2 on day 1 of each cycle for adenocarcinoma or squamous carcinoma; or pemetrexed 500 mg/m 2 plus cisplatin 75 mg/m 2 on day 1 every 3 weeks for non-squamous carcinoma). The primary endpoint was disease-free survival assessed in the full analysis set. Secondary endpoints were overall survival assessed in the full analysis set and safety assessed in all participants who received study drug. This trial is registered with ClinicalTrials.gov, NCT02448797 . Findings: Between June 8, 2015, and August 2, 2019, 322 patients were randomly assigned to icotinib (n=161) or chemotherapy (n=161); the full analysis set included 151 patients in the icotinib group and 132 in the chemotherapy group. Median follow-up in the full analysis set was 24·9 months (IQR 16·6–36·4). 40 (26%) of 151 patients in the icotinib group and 58 (44%) of 132 patients in the chemotherapy group had disease relapse or death. Median disease-free survival was 47·0 months (95% CI 36·4–not reached) in the icotinib group and 22·1 months (16·8–30·4) in the chemotherapy group (stratified hazard ratio [HR] 0·36 [95% CI 0·24–0·55]; p<0·0001). 3-year disease-free survival was 63·9% (95% CI 51·8–73·7) in the icotinib group and 32·5% (21·3–44·2) in the chemotherapy group. Overall survival data are immature with 14 (9%) deaths in the icotinib group and 14 (11%) deaths in the chemotherapy. The HR for overall survival was 0·91 (95% CI 0·42–1·94) in the full analysis set. Treatment-related serious adverse events occurred in two (1%) of 156 patients in the icotinib group and 19 (14%) of 139 patients in the chemotherapy group. No interstitial pneumonia or treatment-related death was observed in either group. Interpretation: Our results suggest that compared with chemotherapy, icotinib significantly improves disease-free survival and has a better tolerability profile in patients with EGFR -mutant stage II–IIIA NSCLC after complete tumour resection. Funding: Betta Pharmaceuticals Translation: For the Chinese translation of the abstract see Supplementary Materials section.